2020
DOI: 10.1017/s0142716419000559
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate attainment in heritage language speakers: Syntactic and morphological knowledge of Italian accusative clitics

Abstract: The acquisition of a heritage language, normally the weaker language of early bilinguals, has been oftentimes defined as incomplete, especially for morphosyntax. As a result, these early bilinguals resemble late bilinguals more than native language speakers, calling into question the role of age of exposure. The effects of syntactic complexity on knowledge of morphosyntactic structures, however, have not been sufficiently considered hitherto. This study investigates age of exposure and syntactic complexity by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…bilinguals, particularly when the two languages spoken are a clitic and a non-clitic language (Belletti et al, 2007;Romano, 2020Romano, , 2021Smith et al, 2022). The study by Smith et al (2023) provides the original dataset used also in the current study, found a differential pattern of clitic production across three groups (monolinguals, attriters, heritage speakers) where all types of clitics (one argument, as in 3 above, or clitic clusters) were significantly fewer in attriters compared to monolinguals, and in heritage speakers compared to attriters.…”
Section: Questionmentioning
confidence: 71%
“…bilinguals, particularly when the two languages spoken are a clitic and a non-clitic language (Belletti et al, 2007;Romano, 2020Romano, , 2021Smith et al, 2022). The study by Smith et al (2023) provides the original dataset used also in the current study, found a differential pattern of clitic production across three groups (monolinguals, attriters, heritage speakers) where all types of clitics (one argument, as in 3 above, or clitic clusters) were significantly fewer in attriters compared to monolinguals, and in heritage speakers compared to attriters.…”
Section: Questionmentioning
confidence: 71%
“…The authors concluded that attrition may affect linguistic phenomena that show optionality due to their collocation at the syntax-pragmatics interface, but not when interpretation does not allow for optionality in the native grammars. Adult heritage speakers as well as L2 speakers of Italian were tested on their abstract representations of clitics in a structural priming task by Romano (2020Romano ( , 2021, which focused on three positional differences featuring different verb types (lexical, causative, and modal) as in 4. The sentences are interpreted by the author as being on a scale of complexity, with lexical verbs originating the least complex sentences (with no dependencies), and modals originating the most complex sentences (with dependency and clitic climbing).…”
Section: Italian Syntactic Competence In Heritage Speakersmentioning
confidence: 99%
“…Despite showing differences with the 'gold standard', heritage grammars seem to share qualitative similarities in their grammar with monolingual speakers more so than with another natural comparator, namely (adult) L2 learners. It seems to be the case that the two populations -heritage speakers and L2 learners-can have similar accuracy (quantity-see Bianchi 2012 and Romano 2020 and subsequent work discussed below), but differ in their linguistic patterns, where heritage speakers are more aligned to monolingual standards (quality-Montrul 2010; Romano 2020). Importantly, comparisons between heritage speakers and L2 speakers are also claimed to be influenced by methodological considerations.…”
Section: Introductionmentioning
confidence: 99%
“…This definition stems from the observation that, at least in some areas of language, their attainment is mostly divergent from the gold standard of adult native monolingual varieties, and it is often less uniform than in the monolingual context, with great individual variation (Montrul 2016). Attainment has been shown to be divergent, for instance, for some aspects of morphology such as agreement in the nominal and verbal domain (e.g., Spanish heritage/English-dominant bilinguals in Scontras et al (2018); Italian heritage/German-dominant bilinguals in Bianchi (2012)), in syntactic dependencies (e.g., in dependencies across an intervener in Russian heritage/English-dominant speakers, Polinsky 2011, in clitic climbing constructions in Italian heritage/Swedish-dominant speakers, Romano (2020Romano ( , 2021), and more (see Polinsky and Scontras (2020) for a recent review).…”
Section: Heritage Languagesmentioning
confidence: 99%